FLORISTIC THE MUNICIPALITY OF PEDRA PRETA-RN: SUBSIDIES FOR FUTURE DEVELOPMENTS - Jeronimo, Carlos Enrique de Medeiros; Santos, Diana Soares dos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
The town of Pedra Preta in the state of Rio Grande do Norte has been the target of numerous claims of enterprises, especially for electric power generation from wind energy. However, the said council is in the Caatinga region of great importance and sensitivity for the northeast region. This paper seeks to situate geographically the area studied, considering not only the physical aspects of regional, but performing a semi-quantitative survey of floristic elements that constitute the zone of influence of the said municipality. Such information could be used for comparative evaluation of aspects / impacts and estimates of scenarios for environmental license in that region. The observations show that the situation of the vegetation in the study area is affected by human action. However, you can still find the natural vegetation of Caatinga of hiperxerófila, composed of its typical species. As the negative impacts to vegetation generated by the implementation of industrial enterprises as well as for the same operation are minimal and reversible, such activities do not show aggressive vegetation of the Caatinga.